Pengaruh Karakteristik Wirausaha, Modal Usaha, dan Strategi Pemasaran terhadap Perkembangan Usaha Kecil dan Mikro di Kota Cimahi - Budi Prasetiyo; Anisa Ernawati (Universitas Diponegoro, 2022)
The purpose of this study was to determine the effect of entrepreneurial characteristics, business capital, and marketing strategies on the development of small and micro businesses in Cimahi city, either partially or simultaneously. This study uses secondary data. The results showed that there was no partial effect of entrepreneurial characteristics and business capital on business development, while marketing strategy had a partial effect on business development, however, jointly, entrepreneurial characteristics, business capital, and marketing strategy had a significant positive effect on business development.